Psychometric Evaluation and Cultural Adaptation of the Indonesian Version of the Knowledge About Schizophrenia Test (KAST) in Family Caregivers - Kurnianingsih T; Chang JY; Afriandi I; Pandia V; Dhamayanti M (Neuropsychiatric Disease and Treatment)
Tuti Kurnianingsih,1 Jin Young Chang,1 Irvan Afriandi,2 Veranita Pandia,1 Meita Dhamayanti3,4 1Department of Psychiatry, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Department of Public Health, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3Department of Child Health, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 4Center for the Study of Health Systems and Education Innovation for Health Workers, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Meita Dhamayanti, Faculty of Medicine, Universitas Padjadjaran, Jalan Ir. Soekarno No.KM. 21, Hegarmanah, Jatinangor, Sumedang Regency, Bandung, West Java, 45363, Indonesia, Email meita.dhamayanti@unpad.ac.idPurpose: The Knowledge about Schizophrenia Test (KAST) is a widely used instrument for assessing knowledge about schizophrenia. However, its applicability in diverse cultural contexts, such as Indonesia, necessitates validation due to potential variations in cultural beliefs and caregiving practices. This study aimed to evaluate the psychometric properties and conduct a cultural adaptation of the Indonesian version of the KAST among family caregivers of individuals with schizophrenia in Indonesia.Methods: A cross-sectional study was conducted involving 94 family caregivers of schizophrenia patients from community settings. Item analysis, construct validity (using known-group comparison and confirmatory factor analysis (CFA)), and internal consistency reliability were assessed.Results: Item analysis indicated acceptable discriminant power for most items, with Pearson correlation coefficients ≥ 0.3, except for item 17 (0.237). Known-group validity, assessed via the Mann–Whitney U-test, demonstrated significantly higher KAST scores in primary caregivers compared to other family members across all three domains (p < 0.0001), indicating strong construct validity. CFA yielded favorable fit indices: χ 2 = 7.5, df = 7, p = 0.379, GFI = 0.99, CFI = 1.00, NNFI = 0.99, RMSEA = 0.02, and SRMR = 0.03. The Kuder-Richardson Reliability Coefficient was 0.872, confirming high internal consistency.Conclusion: The culturally adapted Indonesian version of the KAST demonstrated robust psychometric properties, making it a reliable and valid instrument for assessing schizophrenia knowledge among family caregivers in Indonesia.Keywords: schizophrenia, knowledge, family, caregiver, psychometric evaluation, cultural adaptation, scale validation